2020
DOI: 10.1002/mp.14601
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the differentiation and quantification of high‐Z nanoparticles incorporated in medical devices for CT‐guided interventions

Abstract: Purpose Material differentiation has been made possible using dual‐energy computed tomography (DECT), in which the unique, energy‐dependent attenuating characteristics of materials can provide new diagnostic information. One promising application is the clinical integration of biodegradable polymers as temporary implantable medical devices impregnated with high‐atomic number (high‐Z) materials. The purpose of this study was to explore the incorporation of high atomic number (high‐Z) contrast materials in a bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Using external reinforcement and self-sealing polymers, which have been used in the development of modified AVGs, perivascular scaffolds can also be enhanced to optimize their capacity to provide mechanical support. Despite the fact that bioresorbable polymers are naturally radiolucent, they can also be combined with nanoparticles to give them radiopacity, enabling the tracking of their deployment and breakdown over time [ 94 ]. An all-in-one electrospun perivascular wrap that delivers drugs and/or cells locally while also providing mechanical support for ideal hemodynamics should be possible with the integration of emerging technologies.…”
Section: Future Directionsmentioning
confidence: 99%
“…Using external reinforcement and self-sealing polymers, which have been used in the development of modified AVGs, perivascular scaffolds can also be enhanced to optimize their capacity to provide mechanical support. Despite the fact that bioresorbable polymers are naturally radiolucent, they can also be combined with nanoparticles to give them radiopacity, enabling the tracking of their deployment and breakdown over time [ 94 ]. An all-in-one electrospun perivascular wrap that delivers drugs and/or cells locally while also providing mechanical support for ideal hemodynamics should be possible with the integration of emerging technologies.…”
Section: Future Directionsmentioning
confidence: 99%
“…As in our previous studies, 10,20−22 BiNPs were infused into PPDO monofilament sutures via a wet dipping technique to provide radiopacity to the inherently radiolucent PPDO. One previous study evaluating different high-Z contrast agents showed that Bi has optimal differentiation from iodine in dual-energy CT and has significantly increased contrast for quantification in high-energy singleenergy CT. 11 Moreover, dual-energy CT revealed that BiNP− PPDO IVCFs could be clearly differentiated from injected iodine contrast in a pig model. These promising results could lead to breakthroughs in the noninvasive intraoperative and postoperative CT assessment of bioresorbable medical devices.…”
Section: Resultsmentioning
confidence: 99%
“…BiNPs were synthesized via the thermal decomposition of BiAc 3 in the presence of high-boiling point organic solvents. ,, In detail, 3 mmol BiAc 3 , 50 mL of oleylamine, 20 mL of oleic acid, and 30 mL of 1-octadecene were mixed in a 500 mL three-necked, round-bottom flask and heated at 100 °C with stirring for 1 h. The solution was then heated at 240 °C for 10 min under argon gas protection. A needle was used to vent the argon gas during the synthesis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations